A Survey of Experiences with Emerging Market Sovereign Debt Restructurings. (Policy Papers; Policy Paper, 2012)
This paper takes stock of past episodes of debt restructuring and reviews the relevant literature. Based on cross-country experience from the late 1990s through 2010 of emerging markets it offers some stylized facts.